Impact of a Preemptive Multimodal Analgesia plus Femoral Nerve Blockade Protocol on Rehabilitation, Hospital Length of Stay, and Postoperative Analgesia after Primary Total Knee Arthroplasty: A Controlled Clinical Pilot Study. (30th April 2012) - Beaupre, Lauren A.; Johnston, D. Bill C.; Dieleman, Sherry; Tsui, Ban
Abstract : Purpose . To compare preemptive multimodal analgesia (PMMA) without femoral nerve blocks (FNB) to PMMA including FNB following total knee arthroplasty (TKA). Methods . In a prospective, controlled pilot study, subjects with noninflammatory arthritis undergoing TKA and a short postoperative stay received either PMMA + FNB (FNB group; n = 19 ) or PMMA only (PMMA group; n = 20 ). No preoperative group differences were noted. Evaluations occurred in hospital and at 2, 6, and 12 weeks postoperatively. The primary outcome (knee flexion) was measured on day two postoperatively. Rehabilitation indices, pain, analgesic use, and length of stay (LOS) were also measured. Results . All subjects completed the study. The only significant group differences were quadriceps motor blocks in the FNB group (P < 0.001 ). No significant differences were noted in ROM, pain levels, analgesic use, or hospital LOS. Conclusion . Other than the quadriceps motor block, no group differences were noted; both achieved satisfactory analgesia. Best postoperative pain management strategies when following a short hospital stay program are still unclear.